Efficacy of Medium Cut-Off Dialyzer and Comparison with Standard High-Flux Hemodialysis - Rambabova Bushljetic, Irena; Trajcheska, Lada; Biljali, Sefedin; Balkanov, Trajan; Dejanov, Petar; Spasovski, Goce (S. Karger AG, 2021)
Background: A new medium cut-off (MCO) membranes has been designed to achieve better removal capacities for middle and large middle molecules in hemodialysis (HD) treatment. Aim: The aim of this study was to evaluate the removal efficacy of Theranova® in standard HD in comparison with standard high-flux HD. Methods: Four HD patients (M/F 1/4) were included in 12-week observational pilot study in HD with Theranova® 400 and Theranova® 500 dialyzers. Each patient was assessed 4 times, T0 with high-flux dialyzers, T1 at 1 month, T2 at second month, and T3 at third month, by measuring pre- and post-HD samples of urea, Cr, β2-microglobilin (β2M), myoglobin, albumin, free light chains kappa (FLC-k), and free light chains lambda (FLC-λ). Results: The data showed a higher average removal rate for all the uremic toxins with Theranova® dialyzers for β2M, myoglobin, FLC-k, and FLC-λ (62.7, 56.9, 63.5, and 54.6%, respectively) during the 3 months. Albumin retention was observed and did not change between T0 and T3 (p = 0.379). Conclusion: Compared to high-flux membranes, MCO membranes show greater permeability for middle molecules in midterm report.
Keywords: High-flux dialysis; Medium cut-off membrane; Uremic toxins; Removal rate; Middle molecules